2018
DOI: 10.1021/acsnano.8b04787
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Responsive, Brain-Targeting Nanoparticles for Improved Stroke Therapy

Abstract: Current treatments for ischemic stroke are insufficient. The lack of effective pharmacological approaches can be mainly attributed to the difficulty in overcoming the blood-brain barrier. Here, we report a simple strategy to synthesize protease-responsive, brain-targeting nanoparticles for the improved treatment of stroke. The resulting nanoparticles respond to proteases enriched in the ischemic microenvironment, including thrombin or matrix metalloproteinase-9, by shrinking or expanding their size. Targeted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 37 publications
2
91
0
Order By: Relevance
“…Accordingly, we synthesized maleimide‐terminated PEG‐PCL‐ NECP ‐PEG, or Mal‐PEG‐PCL‐ NECP ‐PEG, which were obtained through the same synthesis procedures as that for PEG‐PCL‐ NECP ‐PEG, except that MAL‐PEG‐OH was used to initiate the ring‐opening polymerization of ε‐caprolactone (Figure S4, Supporting Information). After the nanoprecipitation procedure, Mal‐PEG‐PCL‐ NECP ‐PEG NPs were incubated with AMD3100, which was pre‐thiolated according to our recently published procedure 16a. We characterized and compared the NPs with and without AMD3100 in mice that bear comparable tumor loads (Figure 4c, upper panel), and found that conjugation of AMD3100 significantly enhanced the accumulation of NPs in tumors by 11.9‐fold (Figure 4c,d).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Accordingly, we synthesized maleimide‐terminated PEG‐PCL‐ NECP ‐PEG, or Mal‐PEG‐PCL‐ NECP ‐PEG, which were obtained through the same synthesis procedures as that for PEG‐PCL‐ NECP ‐PEG, except that MAL‐PEG‐OH was used to initiate the ring‐opening polymerization of ε‐caprolactone (Figure S4, Supporting Information). After the nanoprecipitation procedure, Mal‐PEG‐PCL‐ NECP ‐PEG NPs were incubated with AMD3100, which was pre‐thiolated according to our recently published procedure 16a. We characterized and compared the NPs with and without AMD3100 in mice that bear comparable tumor loads (Figure 4c, upper panel), and found that conjugation of AMD3100 significantly enhanced the accumulation of NPs in tumors by 11.9‐fold (Figure 4c,d).…”
Section: Resultsmentioning
confidence: 98%
“…NE‐responsive micellular NPs were synthesized using PEG‐ NECP ‐PCL and PEG‐PCL‐ NECP ‐PEG through the standard nanoprecipitation process 16a. Control non‐responsive NPs were synthesized using PEG‐PCL.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations